Study of a simulator database and an experiment for the evaluation of highway driving safety - Kim, Baeyoung; Jeong, ChoongMin; Suh, Myungwon (Journal of mechanical science and technology, 2011)
Drivers acquire more than 90% of visual information through road signs. However, the road signage along highways can cause driver discomfort and traffic accidents. Conducting experiments along a real highway may cause traffic accidents; therefore, obtaining accurate results from such experiments is difficult. Consequently, this paper reports an experiment for evaluating highway driving safety to reduce the causes of accidents through highway design. It examines the development of a highway database to classify road types in exact accordance with real highways. The study involves an experiment using a driving simulator. The highway database was constructed in two aspects (original and alternative designs) compatible with the DirectX program of Multigen. Four types of physiological measurements (i.e., electrocardiogram, electromyography, electrooculography, and galvanic skin response) were taken from 33 subjects using Biopac equipment in the developed highway database. The skin temperature was measured by a thermal camera. The driver’s state was measured through the Subjective Workload Analysis Technique, NASA-Task Load Index, and Modified Cooper-Harper, among various psychological methods. Statistical analysis was conducted to assure the reliability of the results using the Statistical Package for the Social Sciences 12.0 program.